New mutations, genotype phenotype studies and manifesting carriers in giant axonal neuropathy. Issue 11 (19th June 2007) - Houlden, Henry; Groves, Mike; Miedzybrodzka, Zosia; Roper, Helen; Willis, Tracey; Winer, John; Cole, Gaynor; Reilly, Mary M
Abstract : Giant axonal neuropathy (GAN; MIM 256850) is a severe childhood onset autosomal recessive sensorimotor neuropathy affecting both the peripheral nerves and the central nervous system. Bomont and colleagues identified a novel ubiquitously expressed gene they named Gigaxonin on chromosome 16q24 as the cause of GAN in a number of families. We analysed five families with GAN for mutations in the Gigaxonin gene and mutations were found in four families; three families had homozygous mutations, one had two compound heterozygous mutations and one family had no mutation identified. All families had the typical clinical features, kinky hair and nerve biopsy. We report some unusual clinical features associated with GAN and Gigaxonin mutations as well as confirm the heterogeneity in GAN and the identification of two families with manifesting carriers.